The response of wheat (triticum aestivum L.) vegetative and physiological attributes to salt stress and effect of seed biopriming by Piriformospora indica and Trichoderma virens in improving salinity compatibility - F. Seraj; N. Salimi Tamali; H. Pirdashti; Y. Yaghobian (علوم و فناوری بذر ایران)
The present research was aimed to evaluate the response of wheat vegetative and physiological attributes to seed biopriming by Piriformospora indica (Pi) and Trichoderma virens (Trich). Experiment was conducted as factorial based on completely randomized design with four replicates. Factors were included seven levels of salt stress (0, 40, 80, 120, 160, 200 and 240 mM of NaCl) and four levels of biopriming (control, seed priming by Pi or Trich and dual inoculation by Pi+Trich). Results showed that some measured parameters such as stem diameter, green leaf number per plant, fresh and dry weights of aerial parts and relative water content (RWC) linearly respond to salt stress. These parameters were reduced from 13 to 43 % when salt stress increased from 0 to 240 mM of NaCl. By contrast, some studied parameters such as plant height, stem fresh and dry weights, leaf fresh weight reduced by increasing of salt stress as a segmented equation. Meanwhile, biopriming of Pi and Pi+Trich markedly improved vegetative parameters in addition to RWC in wheat plants. Although, salt stress increased electrolyte leakage seed biopriming could ameliorate its slope as compared to the uninoculated control and therefore prevent its damage to the plant. In conclusion, it seems that seed biopriming of wheat by growth promoting fungi, P. indica and T. virens, positively improved the growth attributes under salt stress conditions.